Pneumocephalus After Dural Puncture During Epidural Analgesia: A Case Report - Mohseni, Gholamreza; Behnaz, Faranak; Tahmasebi, Zahra (International Clinical Neuroscience Journal, 2019)
Lumbar epidural anesthesia commonly used to control post-operation pain. The ‘loss-of- resistance’ to air technique (LORA) generally engaged in the appreciation of the epidural space. One of the rare but serious side effects of this technique is pneumocephalus. We report a case of sudden frontal and parietal headache after a dural puncture during the performance of epidural analgesia using the LOR to air technique.